Which factors determine the upgrading of small and medium-sized enterprises (SMEs)? The case of Egypt - Markus Loewe; Iman Al-Ayouty; Annegret Altpeter; Lisa Borbein; Marc Chantelauze; Maximilian Kern; Elisabeth Niendorf; Malak Reda (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Most low- and middle-income countries have many small but only a few medium-sized and large enterprises. Small firms seem to have difficulties growing into medium-sized ones. This is problematic because medium-sized companies tend to be the main creators of higher quality and better-paid employment, motors of innovation and economic diversification, as well as future exporters. This study focuses on Egypt. It is based on the assumption that while companies grow for various reasons (such as a sudden increase in demand), the only strategy for growth that companies can control is growth through innovation – or `upgrading'. This study investigates the main constraints and success factors for small enterprise upgrading in Egypt. Based on enterprise panel data from 2004 and 2008 and a qualitative in-depth survey, the study concludes that in Egypt the main determinants of upgrading are the entrepreneur's (i) human capital (quality education, work experience and international exposure), (ii) motivation and risk readiness, (iii) investment in human resources, (iv) market research, (v) access to finance and (vi) ability to deal with persistent deficits in the rule of law (especially in state-business interactions such as licensing, taxation and inspections).
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Technologie und Innovation